Optimal sperm length for high siring success depends on forehead patch size in collared flycatchers. (9th August 2018) - Ålund, Murielle; Persson Schmiterlöw, Siri; McFarlane, S Eryn; Qvarnström, Anna
Abstract : When competing over females and fertilization of their eggs, males can use sexual display traits or "competitive" ejaculates, but how these 2 types of characters interact in determining male siring success is unclear. We show that the optimal sperm length, to father offspring in the nest a male attends, differs depending on the size of a sexually selected signal in collared flycatchers. Males with relatively small ornaments benefit from having long sperm, and vice-versa. Abstract: Dominance over rivals, sexual attractiveness, and highly efficient ejaculates are 3 important contributors of male fertilization success but theories about how primary and secondary sexual characters may co-evolve largely remain to be tested. We investigated how variation in a sexual signal (forehead patch size) and sperm morphology jointly affected siring success of 70 males in a natural population of collared flycatchers. We show that the optimal sperm length to attain high relative fertilization success depended on the size of a male's secondary sexual character. Males with small forehead patches sired more offspring in their nest when they produced long sperm and vice-versa. These results are not compatible with theories based on simple relationships between display traits and sperm "quality" but imply that the optimal fertilization strategy (and hence optimal sperm traits) differs between males even in a predominantly socially monogamous population with moderate extra-pair paternity rates. Thus, a better knowledge of the complex chain of behavioural interactions between the sexes and their gametes is needed for a complete understanding of how sexual selection operates in nature.